REWARD AND WORKPLACE ENVIRONMENT ON EMPLOYEE PERFORMANCE AT FACULTY OF ECONOMICS AND BUSINESS SAM RATULANGI UNIVERSITY - Afifah, Addien; Tielung, Maria V.J. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Employee performance is an important thing in a company or organization. It plays a vital role because performance of the company or organization depends on their employee performance. There are several factors that can influence employee performance. Several factors that can considered as the major determinants of employee performance are reward and workplace environment. Reward and workplace environment is used to motivate employee performance to achieve their goal. The objective of this research is to know the influence of reward and workplace environment on employee performance. This research used quantitative method. The method used to analyze the data is the Multiple Regression Analysis. This research uses casual type of research where it will investigate the influence of reward and workplace environment on employee performance. The population observed is the employees of Faculty Economics and Business Sam Ratulangi University (FEB UNSRAT) with sample size as many as 30 respondents. This study reveals those rewards and workplace environment has significant effect partially on employee performance in FEB UNSRAT. Therefore, to increase employee performance of FEB UNSRATreward and workplace environment should be considered intensively. Keywords: employee performance, reward, workplace environment